Navigating the horizon: Healthcare development in 2024 - Subrata, Sumarno Adi; Bayuo, Jonathan (Innovation in Health for Society, 2024)
As we step into the promising realm of 2024, the healthcare landscape is set to undergo transformative changes that promise to redefine patient care, leverage cutting-edge technologies, and address global health challenges. The intersection of innovation, policy reforms, and a collective commitment to improving health outcomes sets the stage for a dynamic year ahead. 2024 marks a pivotal moment in the mainstream integration of precision medicine. Advances in genomics and data analytics enable healthcare providers to tailor treatments based on an individual's genetic makeup, optimizing therapeutic outcomes and minimizing side effects. Keywords: Transformative changes; technology; healthcare system; quality of care; policy reforms